دور التعليم الإلكتروني في تحسين مستوى التدريس من وجهة نظر أساتذة التعميم الثانوي - سالمي, ياسين; بن بردي, إسلام (جامعة الوادي university of Eloued, 2022)
الملخص: عنوان الدراسة هو دور التعليم الإلكتروني في تحسين مستوى التدريس من وجهة نظر أساتذة التعليم الثانوي، فجاءت فرضيات الدراسة على النحو التالي : 1- يؤدي التعليم الإلكتروني إلى تحسين كفاءات تخطيط الدروس لدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة . 2- يؤدي التعليم الإلكتروني إلى تحسين كفاءات تنفيذ الدروس لـدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة . 3- يؤدي التعليم الإلكتروني إلى تحسين كفاءات التقويم لدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة . ولأجل القيام بتطبيق هذه الدراسـة اتبع الباحثان المنهج الوصفي المناسب مع طبيعة الموضوع، ومن أجل التحقق من الفرضيات تم الاعتماد على استبيان التعليم الإلكتروني بعد تحكيمه على عينة الدراسة والتأكد من صدقه وثباته من خلال الدراسة الاستطلاعية ثم قام الباحثان بالدراسة الأساسية على العينة بطريقة المسح الشامل المتكونة من 58 أستاذ من بينهم 26 ذكور و 32 إناث، وهم أساتذة التعليم الثانوي بثانوية بوشوشة بالوادي وباستخدام الأسلوب الإحصائي تمثل في كالاتي: توصلنا إلى : 1- يؤدي التعليم الإلكتروني إلى تحسين كفاءات تخطيط الدروس لدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة . 2- يؤدي التعليم الإلكتروني إلى تحسين كفاءات تنفيذ الدروس لـدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة . 3- يؤدي التعليم الإلكتروني إلى تحسين كفاءات التقويم لدى أساتذة التعليم الثانوي من وجهة نظر الأساتذة Abstract: The title of the study is the role of e-learning in improving the level of teaching from the point of view of secondary education teachers. The study hypotheses are as follows: 1- E-learning improves the lesson planning competencies of teachers secondary school from the point of view of teachers. 2- E-learning leads to improving the efficiencies of lesson implementation among secondary education teachers from the teachers' point of view. 3- E-learning improves the evaluation competencies of secondary education teachers from the teachers' point of view. In order to implement this study, the researchers followed the appropriate descriptive approach with the nature of the subject, and in order to verify the hypotheses, the e-learning questionnaire was relied upon after He judged the sample of the study and ensured its validity and stability through the exploratory study. Then the two researchers conducted the basic study on the sample using the comprehensive survey method, which consisted of 58 professors, including 26 males and 32 females. We have reached an : 1- E-learning improves the lesson planning competencies of secondary education teachers from the teachers' point of view. 2- E-learning leads to improving the efficiencies of lesson implementation among secondary education teachers from the teachers' point of view. 3- E-learning improves the evaluation competencies of secondary education teachers from the teachers’ point of view
دراسة وصفية بثانوية بوشوشة بولاية الوادي
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: التعليم الإلكتروني، التدريس; Apprentissage en ligne, enseignement; E-learning, teaching